Harmonized blank detail specification for lead screw actuated non-wirewound preset potentiometers. Square form, container sealed, actuating device insulated from resistive element, slipping clutch at each end of travel, rigid terminations. Assessment level S. (15th December 1985) - British Standards Institution,
No abstract available